Sound-Evoked Biceps Myogenic Potentials Reflect Asymmetric Vestibular Drive to Spastic Muscles in Chronic Hemiparetic Stroke Survivors - Miller, Derek M.; Rymer, William Z. (Frontiers in Human Neuroscience, 2017)
Aberrant vestibular nuclear function is proposed to be a principle driver of limb muscle spasticity after stroke. We sought to determine whether altered cortical modulation of descending vestibulospinal pathways post-stroke could impact the excitability of biceps motoneurons. Twelve chronic hemispheric stroke survivors aged 46–68 yrs. were enrolled. Sound evoked biceps myogenic potentials (SEBMPs) were recorded from the spastic and contralateral biceps muscles using surface EMG electrodes. We assessed the impact of descending vestibulospinal pathways on biceps muscle activity and evaluated the relationship between vestibular function and the severity of spasticity. Spastic SEBMP responses were recorded in 11/12 subjects. Almost 60% of stroke subjects showed evoked responses solely on the spastic side. These data strongly support the idea that vestibular drive is asymmetrically distributed to biceps motoneuron pools in spastic stroke survivors. This abnormal vestibular drive is very likely to be a factor mediating the striking differences in motoneuron excitability between the clinically affected and clinically spared sides. This study extends our previous observations and potentially sheds light on the underlying mechanisms of post-stroke spasticity.